Extraction of Pectin from Tamarind Fruits (Tamarindus indica L.) and its Utilization in Jam Production - Sulieman, Abdel Moneim E.; Ibnouf, Sulima M.; Hassan, Kamal S. (Gezira Journal of Engineering and Applied Sciences, 2018)
In the present work, pectin was extracted from tamarind fruit pulp and used for jam production. The pectin yield in one kg tamarind pulp was 3.7 grams. The average chemical composition of tamarind pulp was: 5.44 % protein, 2.44 % ash, 18.21 % moisture, 1.99 ± 0.8% fat, 13.05 ± 0.7% fiber and 55% available carbohydrates. The tamarind fruit pulp also contained appreciable amounts of minerals as follows: 134 (mg/100g) sodium, 74 (mg/100g) potassium and 88 (mg/100g) calcium. The chemical, microbiological and sensory quality characteristics of the extracted pectin jam (A) as well as commercial pectin jam (B) were also determined. (A) contained: 8.5 % total sugar, 5 % reducing sugar, 67 % total soluble solid, 36 mg/100g sodium, (60 mg/100g potassium, 80 mg/100g calcium and had a pH value of 3.3. On the other hand, (B) contained:    12 % total sugar, 1.3 % reducing sugar, 68 % total soluble solid, 44 (mg/100g) sodium, 43 (mg/100g) potassium, 64 (mg/100g) calcium and had a pH value of 3.5±0.1. Microbiological analysis of (B) had shown high levels of yeast and mould, however, the counts of yeast and mould was highly reduced in (A). The sensory analysis indicated that all types of jams were accepted by panelists who generally preferred (B) than (A) due to its appealing colour and flavour.